Prevención de la violencia de género y su incidencia en los niños y niñas del estudio de caso en el Centro Infantil Peques Club - Mosquera Andrade, Katherine del Consuelo (2016)
The case study aims to study violence against women and gender and how this affects the Children and the education system, considering the case, PEQUES CHILD CENTER CLUB "and analyze what interests · Impacts gender violence, which is child's Witnesses, often silent and quiet Children of pre-basic of Peques Children's Center Club. quiet and silent or afraid of what they see and live at home, particularly violence Witnesses exerted Parent, stepparents or partners of their mothers, we also believe that children of pre-Shirt ranging between the ages of 4-5 years are promising UN Group of society in which if preventive action should invest shares contribute to changing paradigms dismantle The naturalization of violence against women. In this regard, With This Case Study is expected to consolidate new gender relations based on full respect for the rights and the installation of new forms of discrimination son coexistence and equity; That's why study is the product of reflection and application of a methodology applied with children five to nine years, called the Participatory Route "in leaps and violence put high" Regional Programme "Fighting Violence against Women - ComVoMujer-GIZ "of the German Development Cooperation – GTZ(Cooperación Alemana - ComoVoMujer-GIZ, 2012). The authors of this study were trained and applied the methodology mentioned in the Peques Club Children's Center, with approximately 20 children / as between the ages of 4-5 years as part of the pre-professional training of their teaching career.